Chloride-assisted synthesis of tellurene directly on SiO2/Si substrates: growth mechanism, thermal properties, and device applications. Issue 8 (12th April 2023) - Chan, Yi-Hsun; Lin, Che-Yi; Chou, Yu-Chang; Chang, Alice Chinghsuan; Lin, Yen-Fu; Chen, Yu-Ze
Abstract : The tellurene flakes display outstanding structure stability over 30 days under ambient exposure and reveal the abnormal thermal conductance across grain boundary by exploiting SThM. Abstract : The new single-element two-dimensional materials in the post-graphene era, such as phosphorene and silicene, are emerging as alternative next-generation materials due to their remarkable physical properties. However, the vulnerability of silicene and phosphorene to the air hinders their practical applications. Recently, a new kind of single-element two-dimensional material, namely tellurene, exhibiting outstanding electrical mobility and superior long-term stability in the air, has been successfully synthesized. Here, we report that the addition of chloride (TeCl4 ) to TeO2 is conducive to the lateral growth of tellurium on the SiO2 /Si substrate. The resulting tellurene flakes display outstanding structure stability over 30 days under ambient exposure. Furthermore, the applicability of SThM (scanning thermal microscopy) to investigate the thermal properties of tellurene is presented for the first time, revealing its abnormal thermal conductance across grain boundaries and a thickness-dependent thermal transport behavior. Finally, tellurene-based FETs (field effect transistors) were fabricated, which displayed temperature-dependent I ds that decreased with decreasing temperature rather than metallic transport features, which implies thermal activation of a semiconductor and confirms that the transport follows the 2D variable-range hopping (VRH) model.